Augmented Reality v/s Virtual Reality - Mahato, Nitish (International Journal of Computer Sciences and Engineering, 2025)
This paper presents an impression of basic aspects of Augmented Reality (AR) and Virtual Reality(VR). It defines the main fields in which Augmented and Virtual Reality is applied nowadays and importance of AR and VR devices. Some differences and similarities of Augmented Reality and Virtual Reality will be discussed and this paper will provide an outline of them. Technology is advancing at a abrupt pace as many things that were not possible a few years ago are possible now. Augmented Reality (AR) and Virtual Reality (VR) are a part of these progressive and innovative forms of technologies that were thought as a part of fiction even a few years ago but now they are an important part of the everyday reality